Why so low for so long? A long-term view of real interest rates - Claudio Borio; Piti Disyatat; Mikael Juselius; Phurichai Rungcharoenkitkul (Bank of Finland, 2017)
Prevailing explanations of the decline in real interest rates since the early 1980s are premised on the notion that real interest rates are driven by variations in desired saving and investment. But based on data stretching back to 1870 for 19 countries, our systematic analysis casts doubt on this view. The link between real interest rates and saving-investment determinants appears tenuous. While it is possible to find some relationships consistent with the theory in some periods, particularly over the last 30 years, they do not survive over the extended sample. This holds both at the national and global level. By contrast, we find evidence that persistent shifts in real interest rates coincide with changes in monetary regimes. Moreover, external influences on countries' real interest rates appear to reflect idiosyncratic variations in interest rates of countries that dominate global monetary and financial conditions rather than common movements in global saving and investment. All this points to an underrated role of monetary policy in determining real interest rates over long horizons.
URN:NBN:fi:bof-201712211722
Keywords: E32; E40; E44; E50; E52; 330